Physicochemical and Microbiological Changes in Halal Tipas: Maguindanaon Delight - Guiamalon, Tarhata S. (Journal of Neonatal Surgery, 2025)
As one of their traditional delights, Tipas has been consumed by the Maguindanao people for generations. It is a delicacy that represents the pride and identity of the Maguindanaons. In addition to being served at special occasions, it is sometimes used as a snack as well. This study was conducted to determine the physicochemical and microbiological Changes during storage. The Tipas was packed individually and stored under 30 ± 2 °C (ambient temperature). The samples were analyzed for water activity, microbiological contaminants (Total Plate Count, Yeast and Mold Count, Coliform Count, E. coli, and Salmonella), and sensory attributes (odor, appearance, and flavor/taste) over a period of 3 months, with evaluations at 7 time points: Month 0, 0.5, 1, 1.5, 2, 2.5, and 3. The results show that Tipas is relatively stable in terms of its appearance/color and odor. The microbiological and water activity tests results are all within the set standard limits and the Tipas is stable until the end of shelf-life study. Overall, the Tipas is relatively stable in terms of microbial, organoleptic, and physicochemical properties when stored at 30+2⁰C. The stability of Tipas indicates that it can maintain its quality and safety over time, which makes it a reliable product for consumers. It is important to consider these findings when developing products and marketing strategies. The shelf life of Tipas is three (3) months.